Shades of gray: Understanding the ethics of society's technology and innovation propensities using national culture. (30th August 2022) - Johnson, William H.A.
Abstract : This study examines the effects of national culture on national innovation. This is important because underlying values, which relate to national culture and are the basis of ethical stances, are predicted to affect directly country-level innovation propensities, which then can affect national economic well-being. Combining analyses from two databases, the paper explores the relationships between cultural dimensions, which are manifestations of underlying personal values held across a societal group, and national innovation outcomes. The first database uses Hofstede's national culture dimensions and the other is based on the global innovation index scores of 71 countries. Of the six cultural dimensions, only masculinity/femininity is not found to be significantly related to innovation outcomes. Power distance and uncertainty avoidance negatively relate to innovation outcomes for three and four years, respectively, of the five years tested. Individualism, long-term orientation and indulgence positively relate to innovation outcomes for all five years tested. A major implication is that these cultural variables are important for innovation progress. Findings also suggest that the ethical use of technology and its underlying innovation practices (based on the value systems underlying these cultural dimensions) could benefit from further exploration on the effects of culture. In particular, if a country wants to increase its innovative efforts, it may be well advised to stress individualistic, future-oriented and egalitarian tendencies.